Intra- and inter-observer reliability of determining radiographic sagittal parameters of the spine and pelvis using a manual and a computer-assisted methods. - Dimar JR 2nd; Carreon LY; Labelle H; Djurasovic M; Weidenbaum M; Brown C; Roussouly P; Dimar, John R 2nd; Carreon, Leah Y; Labelle, Hubert; Djurasovic, Mladen; Weidenbaum, Mark; et al. (European Spine Journal, 2008)
Sagittal imbalance is a significant factor in determining clinical treatment outcomes in patients with deformity. Measurement of sagittal alignment using the traditional Cobb technique is frequently hampered by difficulty in visualizing landmarks. This report compares traditional manual measurement techniques to a computer-assisted sagittal plane measurement program which uses a radius arc methodology. The intra and inter-observer reliability of the computer program has been shown to be 0.92-0.99. Twenty-nine lateral 90 cm radiographs were measured by a computer program for an array of sagittal plane measurements. Ten experienced orthopedic spine surgeons manually measured the same parameters twice, at least 48 h apart, using a digital caliper and a standardized radiographic manual. Intraclass correlations were used to determine intra- and interobserver reliability between different manual measures and between manual measures and computer assisted-measures. The inter-observer reliability between manual measures was poor, ranging from -0.02 to 0.64 for the different sagittal measures. The intra-observer reliability in manual measures was better ranging from 0.40 to 0.93. Comparing manual to computer-assisted measures, the ICC ranged from 0.07 to 0.75. Surgeons agreed more often with each other than with the machine when measuring the lumbar curve, the thoracic curve, and the spino-sacral angle. The reliability of the computer program is significantly higher for all measures except for lumbar lordosis. A computer-assisted program produces a reliable measurement of the sagittal profile of the spine by eliminating the need for distinctly visible endplates. The use of a radial arc methodology allows for infinite data points to be used along the spine to determine sagittal measurements. The integration of this technique with digital radiography's ability to adjust image contrast and brightness will enable the superior identification of key anatomical parameters normally not available for measurement on traditional radiographs, improving the consistency of sagittal measurement.